2013
DOI: 10.1371/journal.pone.0082886
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Climate on Host-Parasite Interactions: A Comparative Study of European Birds and Their Parasites

Abstract: BackgroundClimate change potentially has important effects on distribution, abundance, transmission and virulence of parasites in wild populations of animals.Methodology/Principal FindingHere we analyzed paired information on 89 parasite populations for 24 species of bird hosts some years ago and again in 2010 with an average interval of 10 years. The parasite taxa included protozoa, feather parasites, diptera, ticks, mites and fleas. We investigated whether change in abundance and prevalence of parasites was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 53 publications
0
35
0
7
Order By: Relevance
“…Final models were chosen based on lowest AICc scores using model selection functions in R. Significance codes: '*' ≤ 0.05, '**' ≤ 0.01, '***' ≤ 0.001. Disentangling these influences is the topic of previous and ongoing research (Møller et al 2013, Goedknegt et al 2015, Mignatti et al 2016, Gehman et al 2018. λ is an estimate of the phylogenetic signal in the analysis and ranges from 0 (no phylogenetic signal in data) to 1 (Brownian motion).…”
Section: Discussionmentioning
confidence: 99%
“…Final models were chosen based on lowest AICc scores using model selection functions in R. Significance codes: '*' ≤ 0.05, '**' ≤ 0.01, '***' ≤ 0.001. Disentangling these influences is the topic of previous and ongoing research (Møller et al 2013, Goedknegt et al 2015, Mignatti et al 2016, Gehman et al 2018. λ is an estimate of the phylogenetic signal in the analysis and ranges from 0 (no phylogenetic signal in data) to 1 (Brownian motion).…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study found that climate change has already influenced the abundance and distribution of tick species associated with European birds (19), and models found that Ixodes scapularis will expand significantly northward to Canada (20,21). Further, climate warming trends correlated with earlier (as much as 3 weeks) activity of I. scapularis in the spring (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, as global climate and the distributions of other vertebrate hosts change, the environment in the United States may become more suitable for tropical tick species, which might change the risk of tick-borne disease. A recent longitudinal study of European species found that climate change has influenced the distribution and abundance of parasites associated with many bird species, including ticks (19). In North America, the warming climate has also influenced tick species range and phenology (20).…”
mentioning
confidence: 99%
“…The distribution and population of wild boars is increasing because of many factors, such as global climatic change and food resources, and the distribution of wild boars has now extended to the Republic of Korea (ROK) [5–7]. …”
Section: Introductionmentioning
confidence: 99%